2017
DOI: 10.2196/jmir.7303
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Access to Digital Technology in US Young Adults in 2016

Abstract: BackgroundIn 2015, 90% of US young adults with Internet access used social media. Digital and social media are highly prevalent modalities through which young adults explore identity formation, and by extension, learn and transmit norms about health and risk behaviors during this developmental life stage.ObjectiveThe purpose of this study was to provide updated estimates of social media use from 2014 to 2016 and correlates of social media use and access to digital technology in data collected from a national s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 50 publications
3
142
0
7
Order By: Relevance
“…Mobile photo-based assessment of alcohol and food intake may be particularly well suited to young adults, as social media use is extensive in this population [35]. The vast majority of young adults (85%) use photo-based social media apps such as Instagram regularly [35,36], and social media-based apps are often used to display food and beverage intake [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile photo-based assessment of alcohol and food intake may be particularly well suited to young adults, as social media use is extensive in this population [35]. The vast majority of young adults (85%) use photo-based social media apps such as Instagram regularly [35,36], and social media-based apps are often used to display food and beverage intake [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of young adults (85%) use photo-based social media apps such as Instagram regularly [35,36], and social media-based apps are often used to display food and beverage intake [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Research by Byers (as cited in Page and Duffy 2018, p. 7) indicates that 33% of adults younger than 30 years old got news from social networking sites, up from 12.5% in 2010, a 260% increase. Villanti et al (2016), have found that in 2014, 89.42% of young adults reported regular use of at least one social media site. This increased to 97.5% of young adults in 2016.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The connection between illicit access and social media is particularly concerning given that many social media platforms are popular among young adults (a recent 2017 study reported that 30.85% of young adults used Twitter), a population at specific and increasing risk to prescription opioid addiction [38,39].…”
Section: Opioid Challenge: Illicit Online Marketing Of Sale Of Opioidmentioning
confidence: 99%